Exploring Novel Biomarkers of Brain Health in Midlife Type 2 Diabetes Mellitus (ENBIND) - DYER, ADAM HENRY (Trinity College Dublin. School of Medicine. CentreFor Medical Gerontology, 2020)
Type 2 Diabetes Mellitus (T2DM) in midlife (between the ages of 35-65) is associated with a two-fold increased risk of dementia in later life. Despite this, knowledge around the pathophysiological mechanisms linking T2DM and dementia remain poorly explored. Further, knowledge around which individuals with T2DM in particular are at greatest risk of later cognitive decline is lacking. The aim of the current study was to address some of these open questions in a cohort of otherwise healthy individuals with T2DM and matched controls. We aimed to explore the determinants of cognitive function in midlife T2DM and assess the role of markers from two previously unexamined areas to predict deficits in T2DM -namely (i) midlife gait speed and (ii) innate immune system activity. Otherwise healthy individuals with midlife T2DM (aged 35-65) were recruited and had a detailed history obtained and exam performed. Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA) as a measure of general cognition in addition to a detailed computerised neuropsychological assessment (CANTAB) aimed at examining executive function, attention, working memory and reaction time. Gait speed was assessed over three tasks: (i) ‘usual’ or ‘self-selected’ gait speed, (ii) ‘fast’ or ‘maximal’ gait speed as well as (iii) cognitive dual-task gait. Blood samples were taken for assessment of peripheral circulating cytokines (a pre-selected panel of six proteins was assessed) and isolation of Peripheral Blood Mononuclear Cells (PBMCs). PBMCs were stimulated with several innate immune agonists directly chosen to target the innate immune NLRP3 inflammasome. NLRP3 activation was measured as the production of mature IL-1β(an inflammasome dependent cytokine). Overall, participants with midlife T2DM had significantly poorer scores on the MoCA, and were more than twice as likely to make an error as their non-T2DM counterparts. This finding persisted after adjustment for age, sex, years or formal education and a family history of cognitive impairment. We also observed strong trends for poorer performance on neuropsychological tests of executive function, attention, reaction time in T2DM. Those with T2DM had significantly slower gait speed as measured across all three tasks, which persisted after controlling for covariates known to impact on gait speed in midlife. In the overall cohort, slower gait speeds on all three tasks were associated with a greater likelihood of error on the MoCA. Following robust covariate adjustment, only the association for greater dual task cost (a greater slowing effect on addition of the cognitive dual task paradigm) remained significantly predictive of MoCA score. We observed several significant associations between performance on both the self-selected and maximal gait speed tasks and measures of executive function and attention. However, none of the observed effects were specific to those with T2DM as assessed by an interaction term between T2DMstatus and the independent variable of interest incorporated into the regression models.There were no differences between individuals with T2DM and healthy controls in the serum levels of six pro-inflammatory markers. We observed several associations between elevated MCP-1 and greater likelihood of error on the MoCA in addition to associations between MCP-1 and measures of working memory. We demonstrated significant production of IL-1βon stimulation of the NLRP3 inflammasome with several agonists, including Aβ-42, the pathogenic protein in Alzheimer’s Disease (AD). This did not differ between those with T2DM and healthy controls. We observed significant associations between greater inflammasome activation in response to Aβ-42 and greater likelihood of error on the MoCA in addition to poorer performance on the dual-task gait paradigm. There was a strong trend for a T2DM-specific effect. In conclusion, we report significantly poorer cognitive and gait performance in midlife T2DM. Addition of a cognitive-dual task gait greatly enhances the ability of gait assessment to act as a predictor of cognitive performance. Whilst analysis of serum pro-inflammatory cytokines yielded no significant results, we observed significant associations between NLRP3 inflammasome responsiveness to Aβ-42 (and other NLRP3 agonists) and performance on both general cognition (MoCA) and the cognitive dual-task gait paradigm. Future work will follow this cohort to analyse these markers longitudinally, adding further to our insight around the putative pathophysiological and potential underlying mechanisms linking T2DM in midlife and later dementia risk, with the ultimate aim of selecting out those most at risk for multi-domain preventative interventions.
APPROVED